Correction: Investigating and Learning Lessons from Early Experiences of Implementing ePrescribing Systems into NHS Hospitals: A Questionnaire Study. - Kathrin Cresswell; Jamie Coleman; Ann Slee; Robin Williams; Aziz Sheikh; ePrescribing Programme Team (PLoS ONE)
[This corrects the article on p. e53369 in vol. 8.].